Academic writing using artificial intelligence (AI) assistance: methods, applications, and experiences - Sha’ari, ohammad Suhaidi (Faculty of Pharmacy, 2025)
The program "Academic Writing Using Artificial Intelligence (AI) Assistance: Methods, Applications, and Experiences", organised by the Research Empowerment Unit (RAMP-IT) of the Faculty of Pharmacy, UiTM, was successfully executed on Saturday, 13 May 2025, at the Gallery, Level 5, FF1. This full-day workshop (9:00 AM to 4:00 PM) was attended by 29 academic staff members and featured two distinguished experts as speakers: Ts. Dr. Muhamad Fareez Ismail and Associate Professor Dr. Syed Adnan Ali Shah.